2009
DOI: 10.1007/s10194-009-0146-y
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral SUNCT-like headache in a patient with prolactinoma responsive to lamotrigine

Abstract: Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) syndrome is a rare trigeminal autonomic cephalalgia. The cases of SUNCT with attacks that affected both sides simultaneously have only rarely been reported and some of them had underlying pathology. We have reported a case of bilateral SUNCT-like headache secondary to a prolactinoma and responsive to lamotrigine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Other specific cases in which brain tumors have been found in patients with TAC‐like headaches have been reported in the literature 40‐42. One interesting 49‐year‐old male presented with two kinds of right‐sided headache: one similar to cluster headache and one similar to trigeminal neuralgia, which together was felt to be consistent with a cluster‐tic headache.…”
Section: Brain Tumor Headache In General and The Ichdmentioning
confidence: 96%
“…Other specific cases in which brain tumors have been found in patients with TAC‐like headaches have been reported in the literature 40‐42. One interesting 49‐year‐old male presented with two kinds of right‐sided headache: one similar to cluster headache and one similar to trigeminal neuralgia, which together was felt to be consistent with a cluster‐tic headache.…”
Section: Brain Tumor Headache In General and The Ichdmentioning
confidence: 96%
“…23 Another case of bromocriptine-induced SUNCT exacerbation was successfully treated with lamotrigine and the patient could avoid surgical intervention. 24 To our knowledge, this is the first case report of a pediatric patient with a prolactinoma and dopamine agonist-induced migraine exacerbation with a great response and complete control of headache episodes with adjunctive use of low-dose topiramate, which ultimately avoided transsphenoidal surgery. We, therefore, consider that patients presenting with prolactinomas and dopamine agonist-induced headache exacerbations such as migraine or TAC should always be given a trial of preventive medical therapy directed to the primary headache diagnosis before generally labeling them as drug intolerant and referring to neurosurgery.…”
Section: Discussionmentioning
confidence: 86%
“…One case had severe exacerbation of the headache with both bromocriptine and cabergoline and had a dramatic improvement with indomethacin, which further led the authors to classify it as hemicrania continua and made possible for the patient to continue on medical treatment . Another case of bromocriptine‐induced SUNCT exacerbation was successfully treated with lamotrigine and the patient could avoid surgical intervention …”
Section: Discussionmentioning
confidence: 99%
“…We summarized 69 cases of SUNCT-like conditions associated with certain etiologies in 62 English-language studies reported on from 1991 to 2017 and for which there were detailed descriptions of the clinical features and imaging results of the patients. These cases comprised 17 with neoplasm, 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 35 with neurovascular disease, 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 2 with trauma, 44 45 10 with infection, 46 47 48 49 50 51 52 53 54 3 with inflammatory disease, 55 56 57 and 2 with congenital malformation ( Table 1 , 2 , and 3 ). 58 59 …”
Section: Resultsmentioning
confidence: 99%